Kemandirian Anak Saat Learning From Home Terhadap Tingkat Stres Orang Tua - Windy Chintya Dewi; Aironi Zuroida (IDEA: Jurnal Psikologi, 2021)
This study aims to determine the relationship between children's independence when learning from home and the level of parental stress on parents/guardians of elementary/MI students aged 6 to 8 years. The hypothesis of this study is that there is a negative relationship between children’s independence and stress levels in parents. The subjects for this study were 50 parents/guardians across 15 sub-districts of Jombang Regency. The parental stress level scale used was adapted from Abidin's theory. Meanwhile, the children's independence scale was adapted from Havighurst's theory. This data was analysed using SPSS (Statistical Package for Social Science) version 18.0 for Windows. The results showed the Spearman's Rho correlation index rho xy = -0.608 with a significance of 0.000 (p < 0.01). This shows that the hypothesis is accepted with a very significant level. This means that there is a very negative connection between the child's independence and the parents' level of stress. Keywords: Children’s Independence, Parents Stress Level